慢性肝病的评定 (2025)
本发明涉及一种用于评定受试者的慢性肝病的方法，所述方法包括(a)确定来自所述受试者的样品中生物标志物胰岛素样生长因子结合蛋白3(IGFBP3)的量；(b)确定所述样品中生物标志物γ-谷氨酰转移酶(GGT)的量；(c)将步骤(a)和(b)中所确定的所述生物标志物的所述量与针对所述生物标志物的参考进行比较和/或计算用于评定慢性肝病的评分；以及(d)基于步骤(c)中进行的比较和/或计算评定所述受试者的慢性肝病。本发明进一步涉及计算机实现的方法、数据库、装置以及与其相关的用途。 The present invention relates to a method for assessing chronic liver disease in a subject, said method comprising (a) determining an amount of the biomarker Insulin-like growth factor-binding protein 3 (IGFBP3) in a sample from said subject; (b) determining an amount of the biomarker gamma-glutamyltransferase (GGT) in said sample; (c) comparing the amounts of the biomarkers determined in steps (a) and (b) to references for said biomarkers and/or calculating a score for assessing chronic liver disease; and (d) assessing chronic liver disease in said subject based on the comparison and/or the calculation made in step (c). The present invention further relates to computer-implemented methods, databases, devices, and uses related thereto.